2021
DOI: 10.3390/cancers13030438
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers in Childhood Leukemias

Abstract: Involvement of the central nervous system (CNS) in childhood leukemias remains a major cause of treatment failures. Analysis of the cerebrospinal fluid constitutes the most important diagnostic pillar in the detection of CNS leukemia and relies primarily on cytological and flow-cytometry studies. With increasing survival rates, it has become clear that treatments for pediatric leukemias pose a toll on the developing brain, as they may cause acute toxicities and persistent neurocognitive deficits. Preclinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 113 publications
(142 reference statements)
0
7
0
Order By: Relevance
“…The need to understand the causes of metastasis and predict their possible occurrence seems to be a priority task. The attempt to solve this problem most probably is going to be based primarily on molecular biology analysis techniques (Hess et al 2014 ; Ikonomidou 2021 ; Kuehnbaum and Britz-McKibbin 2013 ). Examination of the CSF remains, despite the development of neuroimaging techniques, an essential component of neurological diagnostics.…”
Section: Use Of Csf Metabolomics In Childhood Oncologymentioning
confidence: 99%
“…The need to understand the causes of metastasis and predict their possible occurrence seems to be a priority task. The attempt to solve this problem most probably is going to be based primarily on molecular biology analysis techniques (Hess et al 2014 ; Ikonomidou 2021 ; Kuehnbaum and Britz-McKibbin 2013 ). Examination of the CSF remains, despite the development of neuroimaging techniques, an essential component of neurological diagnostics.…”
Section: Use Of Csf Metabolomics In Childhood Oncologymentioning
confidence: 99%
“…The incidence of CNS involvement is relatively rare but differs depending on the blood cancer subtype. Around 1% of myeloma patients and between 3 and 5% of childhood leukaemia patients have CNS involvement [ 164 , 165 ]. Cytological assessment of CSF to detect CNS involvement suffers from low sensitivity due to contamination with peripheral blood cells and the presence of disease at undetectable levels [ 166 ].…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%
“…However, a study incorporating a larger cohort and longitudinal sampling may reveal significant proteomic changes in the CSF of ALL patients analysed before and during CNS infiltration [ 167 ]. CSF-based biomarkers in childhood leukaemias have recently been reviewed [ 164 ]. A recent study revealed soluble interleukin-2 receptor (IL-2R) levels in CSF as a useful diagnostic indicators of CNS infiltration in haematological malignancies, with the combined analysis of soluble IL-2R and autotaxin improving detection sensitivity in patients with lymphoma [ 163 ].…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%
“…are reported as risk factors of leukemia. 5 Different types of chemotherapeutic drugs, radiation therapy, targeted therapy, and bone marrow transplant, alone or in combination with each other are currently using for treatment of leukemia. 6 In addition, the Immunotherapy which prompts the immune system to identify and destroy cancerous cells is most novel treatment for leukemia.…”
Section: Introductionmentioning
confidence: 99%